Magnetic susceptibility in the superconducting materials - González, J. C. (2009)
Driven by the demand to understand and quantify the magnetic properties of superconducting materials, the ac- and dc-magnetic susceptibility has emerged as a valuable technique in the superconductivity field; allowed us to quantify: superconducting critical temperature, Meissner and diamagnetic shielding fractions, Curie constant, Curie-Weiss temperature and effective Bohr magnetón.